PENULISAN KARYA TULIS ILMIAH DI KELOMPOK KERJA GURU (KKG) SDN SAPEN KECAMATAN BEKONANG KABUPATEN SUKOHARJO - Elis Noviati (Institut Seni Indonesia Surakarta, 2020)
A teacher is a glorious profession. He is demanded to be responsible to educate and to teach the good character to the children. On the other hand, the teachers are demanded to develop their competences on their own field. One thing that becomes their problem is the writing of a working paper. To overcome this problem, the training is held regularly to assist teachers in the writing of working papers. The method used is a model of lectures, assignments, and mentoring. The result of this activity is the teacher can produce at least a working paper. The paper can be included in the scientific journals. Keywords: Teacher, working papers.